Analysis Of Factors Impacting Formation Of The Price Of Silk Products In Uzbekistan - Khudoykulov Mamarasul Radjabovich (Global Scientific Publishing, 2024)
The article is devoted to the consideration of peculiarities of formation of the price of silk products in reliance upon supply and demand. In addition, the article presents analysis of the factors influencing formation of the price of silk products in Uzbekistan. Furthermore, the author analyzes the complex interaction of domestic and global factors on the formation of the price of silk products in Uzbekistan. Moreover, the article presents relevant conclusions and proposals
Keywords: sphere; cluster; demand